Estimation of the environmental service of apprehension of the co 2 in the flora of the humedales of Puerto Viejo - Palomino Contreras, Diana (2007)
Peru is one of twelve countries that concentrates the major biodiversity of the Earth, is characterized by its diversity of ecosystems, species and genetic resources. The human actions are the reason of numerous changes in the natural systems, since it is the case of the climatic global change for the increase in the levels of greenhouse gases (GEI) to the atmosphere, especially of the carbon dioxide (CO2). According to the convention Ramsar (1972); the humedales use as sinks of carbon and the degradation of the humedales will liberate big quantities of carbon dioxide contributing to the increase of the world temperature. In Peru 10 exist humedales protected by the Convention Ramsar. Nevertheless other important humedales exist such it is the case of the Humedales of Old Port that is located in the district of San Antonio, Cañete’s Province, Department of Lima at a height of the km 67.8 - 72.5 of the Panamerican road South. In the present investigation there estimated the environmental service of apprehension of the CO2 of them species of predominant flora being the “ “grama salada” Paspalum vaginatum Swartz, the “Salicornia” Salicornia fruticosa Linneo and the species of handcrafted value as the “totora” Schoenoplectus californicus, and the “junco” Scirpus americanus. where there was quantified the quantity of carbon stored with the purpose of knowing the potential of apprehension of the CO2 of these species typical of the Humedales and hereby to know the loss of these reserves of carbon on having burned them or them to change use for agricultural or urban ends(purposes). This characteristic of capturing carbon gives itself in the biomass air part, radicular and in the soil. In each of these species five were established at random transectos where one took the samples of flora inside these transectos quadrants were established also at random to quantify the herbaceous biomass of the Humedales of Old Port.